Effect of Holding Time on Hardness and Microstructure of AISI 1045 Steel after Carburizing-Quenching Process - Dodi Tafrant; Rachmat Dwi Sampurno; Syamsul Rizal; Dwiki Ramadhani; Ridho Dwi Nopransyah; Wan M. Alif Alhafidz (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
This study investigates the effect of carburising holding time on the hardness and microstructure of AISI 1045 medium-carbon steel after quenching. The carburising process was conducted at 900°C using 100% coconut shell charcoal as the carburising medium, with holding times of 15, 30, 60, and 120 minutes. After carburising, the specimens were directly quenched in lubricating oil without reheating. Five specimens were prepared for each treatment condition, and hardness testing was performed according to ASTM E18 using the Rockwell B hardness scale (HRB). Five hardness measurements were conducted on each specimen to ensure repeatability. The results indicate that increasing holding time improved hardness and promoted martensitic transformation due to deeper carbon diffusion. The average hardness increased from 81.46 HRB for untreated specimens to 94.45 HRB for specimens carburized for 120 minutes. ANOVA analysis confirmed that holding time significantly affected hardness values, and regression analysis yielded an R² of 0.962. Microstructural observations revealed increasing martensite formation with longer holding times. The findings demonstrate that carburizing holding time plays an important role in improving the surface characteristics of AISI 1045 steel. Contribution to Sustainable Development Goals (SDGs):SDG 9: Industry, Innovation and InfrastructureSDG 12: Responsible Consumption and Production